Survey of research on abnormal traffic detection for software defined networks - Yu FU; Kun WANG; Xueyuan DUAN; Taotao LIU (Tongxin xuebao)
Since software defined network (SDN) was more vulnerable to network attacks than traditional networks, the research progress of abnormal traffic detection for software defined network in recent years from the technical principle and architecture characteristics was summarized, the possible organizational forms of network attacks on SDN were analyzed, and the characteristics, advantages, and disadvantages of current technologies related to abnormal traffic detection, abnormal traffic traceability, and abnormal traffic mitigation were discussed.The data sets commonly used in current research were compared and analyzed, and some general data preprocessing methods were sorted out.The research direction of abnormal traffic detection methods in the SDN environment in the future was summarized and prospected.The research results can guide the selection of adaptation methods in practical application requirements, and the problems and contradictions to be solved can guide subsequent research.